Analysis of Student's Engagement in Mathematics Learning Reviewed From the Level of Mathematical Ability of Class XI High School Students - Mustikaningtias, Silvia Yuni; Muliawati, Novita Eka (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
Student involvement is one of the important components and must be given special attention because it is seen as an antidote to low achievement, high levels of despair, high levels of boredom and impoliteness. One of the things that influences engagement is the behavior and personality of students. Through mathematics learning, students are expected to be able to cultivate activeness and skills in receiving material and solving mathematical problems. The purpose of this study is to describe the analysis of student's engagement in mathematics learning with high, medium and low levels of mathematical ability. This type of research is qualitative research using a descriptive approach. The subjects used were 3 students of class XI SMA who were the subject of working on the questions and interview subjects. The authors were the main instruments in this study and supported by supporting instruments such as test sheets and interview guidelines. The results showed: (1) the analysis of student's engagement with high ability in mathematics learning students were able to meet 5 indicators of student engagement, namely related to remembering, related to mathematical fluency, related to personal or community orientation to concepts, related to making combinations and relationships, and related to the accuracy of objectification; (2) analysis of student's engagement; being able to be in mathematics learning students meet 4 indicators of student engagement well related to remembering, related to the fluency of mathematics, related to personal or community orientation to concepts as well as related to making fusions and relationships; (3) analysis of the involvement of low ability students in mathematics learning students can only meet 3 indicators of student engagament well related to remembering, related to the fluency of mathematics as well as related to personal or community orientation to concepts, methods, traits, relationship and implications